ALERTA NACIONAL AND THE STEREOTYPING OF WOMEN'S IMAGES IN PRIME TIME ON BRAZILIAN TELEVISION - da Conceição Veloso, Ana Maria (2022)
This paper aims to analyze women’s images in the narrative of the Brazilian TV show Alerta Nacional, presented bySikêra Junior, who is accused of systematically violating human rights. Programs aired in 2021 were analyzed with the categorization of findings and using content analysis method.The results, understood from the combination of bibliographic research on communication and gender and the role of the media in the elaboration of public image, point to the stereotyping of women and the violation of their rights, contributing to the reinforcement of social roles relegated to subordination.   Keywords: women; media; gender; Sikêra Junior.